Model of packet transmission of text data using SDR in the GNU Radio Companion environment - Kaliaskarov, Nurbol; Taissariyeva, Kyrmyzy; Raulyev, Nurlykhan; Sabibolda, Akezhan (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2026)
This paper outlines the design, implementation, and testing of a digital transmission system capable of sending text data in packetized form using QPSK modulation. The setup leverages Software-Defined Radio (SDR) hardware in combination with GNU Radio Companion software. The system operates by initiating transmission from a configured source, transmitting the data wirelessly, and recovering the signal at the receiver end for decoding and analysis. Two configurations were tested: one using a pseudo-random bit sequence and another using actual file input with both source and channel coding mechanisms. Signal behavior was examined at various stages in the processing chain, including modulation, filtering, over-the-air transmission, synchronization, equalization, and phase correction. Analytical tools such as constellation plots, IQ diagrams, and spectral analysis were employed to evaluate system performance and signal integrity. The model successfully demonstrated reliable data transmission and reconstruction, making it a useful platform for both educational purposes and further exploration in the area of digital communications.